Logros académicos e inclusión social de personas sordociegas mediante la tecnología: Historia de vida - Ramirez Beltran, Freddy Efraín; Rueda Ortíz, Armando Marcelo; García-Cobas, Rudy; Tapia-Leon, Mariela (Revista Minerva, 2024)
This article provides a biographical profile of Sonia Margarita Villacrés Mejía, a person who became deafblind due to an accident at the age of 12. Despite this adversity, Sonia has shown remarkable perseverance and motivation, managing to obtain several academic degrees at both the third and fourth levels. Technology has played a crucial role in her personal and professional life, allowing her to overcome significant challenges. The general objective of this research was to investigate the life story of Sonia Villacrés, focusing on her academic achievements, her educational and social inclusion, and highlighting the role of technology in these aspects. This research, based on documentary and life history methods, investigates the life of Sonia Villacrés and also describes the technological tools she used to improve her quality of life as a deafblind person. To collect data, a documentary analysis was carried out from various sources on the Internet, such as: texts, videos, websites, and interviews. The main result is her fervent support for the educational inclusion of people with disabilities. To publicize the life story of Sonia Villacrés and highlight the role of technology, a website was designed to collect and share this information with society.